Correlation between Semen Quality, Libido, and Testosterone Concentration in Bali Bulls - Hikmayani Iskandar; Herry Sonjaya; Raden IIS Arifiantini; Hasbi Hasbi (Indonesian Center for Animal Research and Development (ICARD), 2022)
Indonesia has two National Artificial Insemination Centers (AIC) and more than 15 Regional Artificial Insemination Centers (RAIC) spread across several provinces. Bulls in the AIC must have a high libido and produce good quality semen. This study examines the correlation between libido with semen quality and testosterone concentration to determine potential frozen semen production from Bali bulls in South Sulawesi RAIC. Ten Bali bull were used in this study. Semen collection was carried out twice a week with semen evaluation following the RAIC protocol. At the same time, blood samples and libido measurements were carried out from each bull. The frozen semen production potential was calculated by multiplying the semen volume, motility, and sperm concentration. The results showed that the quality of fresh semen and testosterone concentrations did not differ between high and low libido of Bali bulls. Libido has a positive correlation with semen volume (r= 0.52) and sperm motility (r= 0.62), while testosterone concentration has a negative correlation with semen volume (r= -0.65), sperm motility (r= -0.60), and libido (r= -0.48). Bulls with high and low libido have good frozen semen production potential, ranging from 19,755 – 21,640 straws per year. Bali bulls in RAIC have fresh semen quality and testosterone concentrations under normal conditions, with high potential for frozen semen production, although only 60% of Bali cattle have high libido and 40% have low libido.